2022
DOI: 10.2217/pmt-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Using Quantitative Sensory Testing to Predict Attrition in an Interdisciplinary Pain Management Program: A Pilot Study

Abstract: Aim: To determine the extent to which quantitative sensory testing (QST) predicted attrition in an interdisciplinary pain program (IPP). Patients & methods: Participants (n = 53) enrolled in an IPP completed pretreatment assessments of QST and the PROMIS-29 quality of life survey. Results & conclusion: Compared with completers, non-completers (24.5%) reported significantly higher pain intensity (7.1, 95% CI [5.8, 8.4] versus 5.4, 95% CI [4.8, 6.1]) and cold hyperalgesia (14.6°C, 95% CI [8.8, 20.4] vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Hardman et al (2019) found higher pain catastrophizing to predict attrition. Zafereo et al (2022) found pain intensity and cold hyperalgesia predicted dropout.…”
Section: Ipp Attrition Is High and Variablementioning
confidence: 88%
“…Hardman et al (2019) found higher pain catastrophizing to predict attrition. Zafereo et al (2022) found pain intensity and cold hyperalgesia predicted dropout.…”
Section: Ipp Attrition Is High and Variablementioning
confidence: 88%
“…Similarly, Dursteler and colleagues showed that low descending pain inhibition, i.e., low conditioned pain modulation (CPM), as assessed by QST was associated withincreased risk for persistent pain following knee replacement surgery [40]. Zaferio and colleagues used QST findings to predict which participants would complete a pain management program and get relief [41]. And Stark weather and colleagues were able to differentiate patients with sustained low back pain from those whose pain resolved based on their results of thermal QST [42].…”
Section: Qst In Precision Pain Managementmentioning
confidence: 99%